Charity and debt behaviors comparison: perception of low-income households. Issue 4 (28th August 2021) - Arsyianti, Laily Dwi; Kassim, Salina
Abstract : Purpose: This paper aims to investigate low-income households in Indonesia with regard to their perspective on charity-giving and its comparison with acquiring debt behavior as their tendencies on taking and giving behaviors toward monetary form. The research framework is seen from the Islamic perspective. Design/methodology/approach: Theory of social production function and theory of planned behavior are used as a theoretical framework. A total of 98.89% of the distributed questionnaires were collected and analyzed using structural equation modeling. Behavior of giving charity and acquiring debt are compared according to the given determinants. Findings: Under the given Islamic framework, charity is found to be not confined to the donor's wealth. It is rather centered on religiosity and faith. Subjective norm does not influence intention toward charity. Hence, it only depends on consideration and awareness of a person toward regular giving of charity. Unlike debt that is confined by a person's wealth, the intention to take debt consecutively of low-income households are also affected by their attitudes, significant others and experiences. Research limitations/implications: Respondents are residents of six Indonesian territories that represent West, Middle and East Indonesia. Practical implications: Findings are useful for social, as well as microfinance practitioners who are interested in the financial education on low-income households and study their perspective and behavior. Social implications: This paper indirectly contributes to changing the perspective of society about charity-giving, especially in philanthropy subject. This paper is also highly recommended for regulator's input on financial education, as well as for practitioners, consultants and educators. Originality/value: Charity basically can assist low-income households experiencing financial hardship, which may be the consequence of consecutive taking debt. Most of the studies on charity-giving focus on high-income households, likewise the debt behavior. Charity-giving in voluntary form is also not widely discussed in view of behavior, specifically in Asian countries like Indonesia.